2020
DOI: 10.1128/jvi.01669-20
|View full text |Cite
|
Sign up to set email alerts
|

Simian-Human Immunodeficiency Virus SHIV.C.CH505 Persistence in ART-Suppressed Infant Macaques Is Characterized by Elevated SHIV RNA in the Gut and a High Abundance of Intact SHIV DNA in Naive CD4 + T Cells

Abstract: Mother-to-child transmission of HIV-1 continues to cause new pediatric cases of infection through breastfeeding, a setting where it is not always possible to initiate early antiretroviral therapy (ART). Without novel interventions that do not rely on daily ART, HIV-1 infected children face lifelong medications to control infection. A detailed analysis of virus persistence following breastmilk transmission of HIV-1 and ART has not been performed. Here, we used infant rhesus macaques orally-infected with simian/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 71 publications
0
46
0
Order By: Relevance
“…Nearly all natural routes of HIV-1 acquisition result from transmission across mucosal surfaces, the exceptions being intrauterine and intravenous infections. Previously, we showed that SHIVs BG505, CH505, and D.191859 can be transmitted efficiently across rectal, vaginal, and oral mucosae ( 17 , 35 ), resulting in productive clinical infection with virus replication kinetics and plasma virus titers indistinguishable from human infections by HIV-1 ( 69 , 70 ). Penile acquisition is another important route of HIV-1 transmission in humans ( 78 ), and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all natural routes of HIV-1 acquisition result from transmission across mucosal surfaces, the exceptions being intrauterine and intravenous infections. Previously, we showed that SHIVs BG505, CH505, and D.191859 can be transmitted efficiently across rectal, vaginal, and oral mucosae ( 17 , 35 ), resulting in productive clinical infection with virus replication kinetics and plasma virus titers indistinguishable from human infections by HIV-1 ( 69 , 70 ). Penile acquisition is another important route of HIV-1 transmission in humans ( 78 ), and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Simian-human immunodeficiency virus (SHIV) infection of Indian rhesus macaques (RMs) is an important outbred animal model for studying HIV-1 transmission, prevention, immunopathogenesis and cure (1)(2)(3). Such research is especially timely, given recent progress with active and passive immunization (4)(5)(6)(7)(8)(9)(10)(11) and novel approaches to HIV-1 cure (https://www.niaid.nih.gov/diseases-conditions/hiv-cure-research) (12)(13)(14)(15)(16)(17)(18), all of which can benefit from rigorous testing and iterative refinement in animal models. Given the multifaceted roles of HIV-1 envelope (Env) in cell tropism and virus entry, and as a target for neutralizing and non-neutralizing antibodies, the particular features of HIV-1 Envs that are selected for SHIV construction and analysis are of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reduced Tfh in RP infants, and associated reductions in active germinal centers, may also be attributed to spatially altered CXCL13 expression impaired homing of T cells into B cell follicles. Specific infection of Tfh cells by HIV and SIV has been observed in both adult and infant macaques [ 53 56 ], yet rather than direct infection driving Tfh loss, infected Tfh cells are reported to serve as sanctuaries for viral persistence [ 53 ]. While RNAscope identified similar levels of cell free virus within B cell follicle light zones between RP and TyP infants ( Fig 9 ), the majority of SIV-infected cells, as well as the brightest areas of MX1 staining, were observed on the border of the B cell follicle, which can be populated by Tfh as well as other CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence for both expansion as well as early depletion of Tfh cells during SIV infection (53, 54), it is poorly understood whether loss of Tfh cells, and their precursors, may be attributed to direct killing from SIV or to aberrant inflammatory signaling driving apoptosis (46,54). Selective infection of Tfh cells by HIV and SIV has been observed in both adult and infant macaques (55)(56)(57)(58), yet rather than direct infection driving Tfh loss, infected Tfh cells are reported to serve as sanctuaries for viral persistence (55). Interestingly, adult macaques exhibiting a more rapid disease progression have trended toward lower proviral DNA levels in Tfh compared to those with more typical disease severity (54).…”
Section: Discussionmentioning
confidence: 99%